Self-regulation as a stronger predictor than motivation of translation competence: a mixed-methods study of undergraduate translation students - Xu, Dan; Guénier, Amily D. Wang (Frontiers in Psychology, 2025)
IntroductionThis study moves beyond the traditional focus on motivation to critically examine the dominant role of self-regulation in shaping translation competence within a flipped classroom setting.MethodsA mixed-methods design was employed with data collected from 131 undergraduate translation students through questionnaires, translation tests, and interviews. Regression analyses were used to assess the predictive strength of motivation and self-regulation, and qualitative interviews provided further insights into students’ learning experiences.ResultsThe findings reveal that while motivation initiates learner engagement, it is self-regulation—encompassing goal-setting, self-monitoring, and strategic adaptation—that ultimately determines students’ ability to navigate the complex demands of translation tasks. Regression results confirmed that self-regulation is a stronger and more consistent predictor of translation competence than motivation. Qualitative data further showed that highly motivated students without self-regulatory strategies often struggled to succeed.DiscussionThese results highlight the limitations of motivation alone and call for a paradigm shift in translator education. Pedagogical models should move beyond motivation enhancement to explicitly cultivate learners’ self-regulation skills. Embedding cognitive and metacognitive training into translation curricula can better prepare students for the complexities of professional practice. This study contributes empirical evidence and pedagogical insights to both translation studies and educational psychology, advocating the development of strategic, self-directed translation professionals.